Laser powder bed fusion of a novel high-strength Al–Mg–Er–Zr-Sc alloy: Process, microstructure, and performance - Zhengjiang Gao; Hui Li; Teng Ma; Huan Yang; Wei Wang; Wu Wei; Hui Huang; Shengping Wen; Zuoren Nie (Journal of Materials Research and Technology, 2025)
In this work, a novel high-strength Al–Mg–Er–Zr-Sc alloy was fabricated by laser powder bed fusion (LPBF). The effects of laser power and scanning speed on the internal defect, density, and microstructure were systematically investigated, and their correlation with alloy microhardness, mechanical strength and elongation were also explored. The results show that alloy exhibits good processability with a wide process window. Alloy strength and microhardness are mainly associated with grain size, precipitation phase size and its distribution. Grains as well as precipitation phases become finer and precipitation density is increased as scanning speed increases or laser power decreases, leading to an enhancement in alloy strength and microhardness. The elongation is closely related to alloy density, which first increases and then decreases with the rising volumetric laser energy density, accompanied by the transformation of internal defects from unfused defects to pores and then to keyholes. Both of keyholes caused by excessive energy input and unfused defects caused by insufficient energy input will decrease alloy density and induce stress concentration, resulting in a reduction in elongation. And compared with keyholes, unfused defects are more detrimental to material elongation and should be avoid in production. Under appropriate process parameters, alloys with density over 99.8 % can be obtained, and can achieve a good combination of strength and plasticity, with a yield strength of 521 MPa, a tensile strength of up to 531 MPa and an elongation of 12 % after heat treatment.